2022
DOI: 10.1002/path.5842
|View full text |Cite
|
Sign up to set email alerts
|

Indoleamine 2,3‐dioxygenase (IDO)‐1 and IDO‐2 activity and severe course of COVID‐19

Abstract: COVID-19 is a pandemic with high morbidity and mortality. In an autopsy cohort of COVID-19 patients, we found extensive accumulation of the tryptophan degradation products 3-hydroxy-anthranilic acid and quinolinic acid in the lungs, heart, and brain. This was not related to the expression of the tryptophan-catabolizing indoleamine 2,3-dioxygenase (IDO)-1, but rather to that of its isoform IDO-2, which otherwise is expressed rarely. Bioavailability of tryptophan is an absolute requirement for proper cell functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 24 publications
0
26
0
Order By: Relevance
“… 38 When specified, the majority of studies described IDO1 induction in lung epithelial cells and 2 studies reported IDO2 induction in lung epithelial cells: in mice following Chlamydia infection 39 and in lung tissue from patients who died of SARS-CoV-2 infection. 40 Notably, in the Chlamydia study, immunohistochemistry revealed IDO1-2 positive bronchial epithelial cells even in uninfected non-infiltrated lung tissue.…”
Section: Lung Cell Types Expressing Kynurenine Pathway Enzymes or Met...mentioning
confidence: 80%
“… 38 When specified, the majority of studies described IDO1 induction in lung epithelial cells and 2 studies reported IDO2 induction in lung epithelial cells: in mice following Chlamydia infection 39 and in lung tissue from patients who died of SARS-CoV-2 infection. 40 Notably, in the Chlamydia study, immunohistochemistry revealed IDO1-2 positive bronchial epithelial cells even in uninfected non-infiltrated lung tissue.…”
Section: Lung Cell Types Expressing Kynurenine Pathway Enzymes or Met...mentioning
confidence: 80%
“…IDO is a crucial enzyme in the Tryptophan‐Kynurenine pathway, and an innate immune inhibitor produced endogenously by epithelial and dendritic cells 19 . The enzyme's activity can usually be expressed by the ratio of K/T 20 . When dendritic cells are stimulated by pro‐inflammatory factors, including IFN‐γ, tumor necrosis factor α, and interleukin‐6, the activity of IDO increases, leading to the accumulation of kynurenine 21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…19 The enzyme's activity can usually be expressed by the ratio of K/T. 20 When dendritic cells are stimulated by pro-inflammatory factors, including IFN-γ, tumor necrosis factor α, and interleukin-6, the activity of IDO increases, leading to the accumulation of kynurenine. 21,22 This, through the aryl hydrocarbon receptor pathway, diminishes the ability of lung epithelial cells to produce immune mediators and suppresses the activity of CD4 + T cells, thereby preventing Th cell-mediated immune injury induced by acute infections.…”
Section: Tryptophan-kynurenine Pathway Regulates the Body's Immune Fu...mentioning
confidence: 99%
“…Anthranilic acid concentrations in the plasma robustly correlate with circulating interleukin-10 and -18 levels [ 41 ]. Moreover, 3-hydroxy-anthranilic acid was found to be accumulated in the brain, heart, and lung from COVID-19 patients, but this accumulation, which was detected on autopsy material, was correlated with the expression of the IDO2 isoform, not IDO1 [ 97 ]. Interestingly, anthranilic acid has been also associated with the risk of developing severe dengue fever, suggesting that this metabolite might be endowed with broad pro-inflammatory properties [ 98 ].…”
Section: Mechanistic Biomarkers Of Covid-19mentioning
confidence: 99%